Post caesarean scar endometriosis: reporting three cases - Thakur, Ruchi; Sambarey, Pradip W.; Katha, Desai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Scar endometriosis remains under diagnosed entity. A high index of suspicion is required for correct diagnosis. Complaints of pain, increase in size or bleeding from a mass post operatively that is cyclically associated with menstrual cycle is almost pathognomonic. Surgical excision remains the treatment of choice. We report three cases treated in our institute.